2015
DOI: 10.1371/journal.pone.0137501
|View full text |Cite
|
Sign up to set email alerts
|

Grit and Work Engagement: A Cross-Sectional Study

Abstract: Grit, defined as perseverance of effort and consistency of interest, has attracted attention as a predictor of success in various fields beyond IQ and the Big Five personality dimension of Conscientiousness. The purpose of the current study was to examine previously uninvestigated questions regarding grit using a cross-sectional design among a large number of working adults in Japan. First, we tested geographical generalizability of associations between grit and orientations towards happiness by comparing prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
109
3
14

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 21 publications
(36 reference statements)
10
109
3
14
Order By: Relevance
“…Perhaps individuals from collectivistic cultures are motivated to persevere as a way to contribute to their families and communities, regardless of their level of personal interest or investment. For example, in a study of Japanese participants, grit was positively correlated with an orientation toward altruistic meaning, but not individual engagement (Suzuki, Tamesue, Asahi, & Ishikawa, ). Surprisingly, the total score reliability for Southeastern Asia was equivalent to the total sample value, with an observed subscale correlation of .19.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps individuals from collectivistic cultures are motivated to persevere as a way to contribute to their families and communities, regardless of their level of personal interest or investment. For example, in a study of Japanese participants, grit was positively correlated with an orientation toward altruistic meaning, but not individual engagement (Suzuki, Tamesue, Asahi, & Ishikawa, ). Surprisingly, the total score reliability for Southeastern Asia was equivalent to the total sample value, with an observed subscale correlation of .19.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, personality factors are found to be critical for student achievement (Poropat, ). For the past few years, a growing body of studies has indicated that grit, a newly explored personality trait, plays a crucial role in personal achievement (Duckworth, Peterson, Matthews, & Kelly, ; Duckworth and Quinn, ; Duckworth, Quinn, & Seligman, ; Duckworth, Kirby, Tsukayama, Berstein, & Ericsson, ; Eskreis‐Winkler, Shulman, Beal, & Duckworth, ; Kelly, Matthews, & Bartone, ; Maddi, Matthews, Kelly, Villarreal, & White, ; Reed, Pritschet, & Cutton, ; Suzuki, Tamesue, Asahi, & Ishikawa, ). The concept of grit was first introduced by Duckworth and her colleagues, who defined it as a person's tendency to sustain continual perseverance and passion for achieving long‐term goals (Duckworth et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, grit received increasing attention from both researchers and practitioners. As an important noncognitive indicator, grit has been used to understand individual success and performance in various fields, such as engagement and performance in the workplace (Suzuki, Tamesue, Asahi, & Ishikawa, ), academic performance and student retention in school (Ivcevic & Brackett, ; Maddi, Matthews, Kelly, Villarreal, & White, ), as well as the effectiveness and performance of teachers (Duckworth, Quinn, & Seligman, ).…”
Section: Introductionmentioning
confidence: 99%